Numerical study on river bar response to spatial variations of channel width. (July 2016) - Duró, Gonzalo; Crosato, Alessandra; Tassi, Pablo
Highlights: We investigate the effects of channel width variations on bar formation. The findings could be used to guide river management or restoration projects. Lateral width reductions can supress bars or fix their location to place an intake. A symmetric widening can force central bars and free a reach from alternate bars. Flow asymmetries after a widening produce mode interactions and compound bar modes. ABSTRACT: Managing river bar formation in alluvial channels remains a challenging issue related to the need to free intakes, improve navigation and optimise river restoration works. This work studies the effects of locally varying the channel width on bar formation to see whether channel widening and narrowing could be feasible bar control measures. The investigation focuses on steady (hybrid) bars, the most common type of bars in lowland rivers. Several numerical experiments are performed using a two-dimensional physics-based finite-difference code. Model simplifications include capacity-limited sediment transport, uniform grain size and constant discharge. Previous tests on field and experimental data show that the simulations of the relevant processes are realistic. The results indicate that the formation of steady alternate bars downstream of lateral structures occurs at a distance that depends on the local width reduction and that narrowing the channel for a distance of 10 times the original width appears sufficient to locally suppress alternate bars. A symmetric inflow forces the formation of symmetric bed topography, as for instance a flat bed or central bars. Similarly, an asymmetric inflow forces asymmetric bed topography, as alternate bars. Upstream flow asymmetries disrupt the symmetry of central bars leading to a compound bed configuration characterised by a dominant wandering channel, a common feature in wide lowland rivers. Central and alternate bars are found to coexist even if bar stability theories predict the development of alternate bars only. These results are promising and raise fundamental questions, but need experimental and field confirmation.